Evaluation of Liquid From the Papanicolaou Test and Other Liquid Biopsies for the Detection of Endometrial and Ovarian Cancers. Issue 8 (August 2018) - Wang, Yuxuan; Li, Lu; Douville, Christopher; Cohen, Joshua D.; Yen, Ting-Tai; Kinde, Isaac; Sundfelt, Karin; Kjær, Susanne K.; Hruban, Ralph H.; Shih, Ie-Ming; Wang, Tian-Li; Kurman, Robert J.; et al.
Abstract : (Abstracted from Sci Transl Med 2018;10:eaap8793) Although the Papanicolaou (Pap) test has dramatically decreased mortality from cervical cancer in the screened population, the test generally is unable to detect endometrial or ovarian cancers. These 2 cancers are usually diagnosed at an advanced stage when the prognosis is poor and treatment does not increase relative survival.